High-temperature piezoelectric ceramic material as well as preparation method and application thereof

By doping (LiMn) 5+ and Ce4+ ions in calcium bismuth tantalate (CaBi2Ta2O9)-based ceramic materials, the problems of low piezoelectric constant and large temperature drift are solved, and stable performance improvement and resistivity improvement at high temperatures are achieved.

CN119859060AActive Publication Date: 2025-04-22SHANDONG LIANS INTELLIGENT TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510345216.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The piezoelectric constant of the bismuth calcium tantalate (CaBi2Ta2O9)-based ceramic materials is too low, and the temperature drift of the piezoelectric constant is also large, resulting in unstable performance when applied at high temperatures.

Method used

The structure and electrical properties of the material are adjusted by quantitatively doping (LiMn) 5+ composite ions at A position and doping Ce4+ ions at B position in calcium bismuth tantalate (CaBi2Ta2O9)-based ceramic material.

Benefits of technology

While ensuring that the Curie temperature does not drop, the piezoelectric constant, thermal stability and resistivity of high-temperature piezoelectric ceramic materials are improved, dielectric loss is reduced, and the piezoelectric constant temperature drift is small, which is suitable for long-term and stable operation at 650℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859060A_ABST
    Figure CN119859060A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature piezoelectric ceramic material and a preparation method and application thereof.The preparation method of the high-temperature piezoelectric ceramic material comprises the steps that a Ca source, a Li source, a Mn source, a Bi source, a Ta source and a Ce source are mixed to obtain a mixture, the mixture is evenly mixed and pre-sintered, and a pre-sintered material is obtained; uniformly mixing the pre-sintered material, granulating, carrying out vacuum packaging, and carrying out warm isostatic pressing to obtain a green body column; carrying out glue removal treatment on the green body column, and sintering for the first time to obtain a ceramic material; and sequentially carrying out high-temperature silver paste coating, secondary sintering and silicone oil medium-high-voltage polarization on the ceramic material to obtain the high-temperature piezoelectric ceramic material. According to the ceramic material, Ca is replaced by composite ions, Ta is replaced by Ce < 4 + >, and the doping amount of Ce < 4 + > is controlled, so that compared with a bismuth calcium tantalate-based ceramic material, the piezoelectric constant, thermal stability and resistivity of the high-temperature piezoelectric ceramic material are improved while the Curie temperature is not reduced, and the dielectric loss is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric ceramics, and in particular relates to a high-temperature piezoelectric ceramic material and a preparation method and application thereof. Background Art

[0002] Bismuth layered piezoelectric ceramics, such as Bi4Ti3O 12 、CaBi4Ti4O 15 Bismuth layered piezoelectric ceramics are composed of perovskite layers and bismuth oxide layers arranged in a specific structure according to certain rules. Bismuth layered piezoelectric ceramics have the characteristics of high Curie temperature, low aging rate, high dielectric breakdown strength and high mechanical quality factor, and have higher resistivity than some traditional piezoelectric ceramics at high temperatures, and stable piezoelectric properties. Bismuth layered piezoelectric ceramics are a type of high-temperature piezoelectric material with great development prospects, and are also the preferred piezoelectric ceramic material for high-temperature piezoelectric vibration sensors in the world. The calcium bismuth tantalate (CaBi2Ta2O9) based ceramic material in the bismuth layered piezoelectric ceramics has a Curie temperature of up to 940°C and a piezoelectric constant of d 33 It is about 5pC / N, which is the most promising piezoelectric ceramic material for high-temperature sensors working at 650 ℃. However, in actual application, the piezoelectric constant of calcium bismuth tantalate (CaBi2Ta2O9)-based ceramic materials is too low, and the temperature drift of its piezoelectric constant (i.e. the change of piezoelectric constant with temperature) is also too large. Therefore, how to improve the piezoelectric constant, resistivity and thermal stability of CaBi2Ta2O9-based ceramic materials without sacrificing the Curie temperature is a key issue. Summary of the invention

[0003] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing a high-temperature piezoelectric ceramic material. The preparation method comprises doping (LiMn) at the A position in a calcium bismuth tantalate (CaBi2Ta2O9) based ceramic material. 5+ Composite ions (Li and Mn simultaneously replace the A position in the crystal to maintain the electrical neutrality and structural stability of the crystal), Ce doping at the B position 4+ Ions are modified.

[0004] Another object of the present invention is to provide a high-temperature piezoelectric ceramic material obtained by the above preparation method.

[0005] The purpose of the present invention is achieved through the following technical solutions.

[0006] A method for preparing a high-temperature piezoelectric ceramic material comprises the following steps: Step 1, mixing a Ca source, a Li source, a Mn source, a Bi source, a Ta source and a Ce source to obtain a mixture, mixing the mixture evenly, and pre-sintering at 850-950° C. for 2-4 hours to obtain a pre-sintered material, wherein, in terms of the amount of substance, the ratio of Ca in the Ca source, Li in the Li source, Mn in the Mn source, Bi in the Bi source, Ta in the Ta source and Ce in the Ce source is 0.5:0.5:0.5:2:(2-0.4x):x, wherein 0.03<x<0.11; In step 1, the Ca source is CaCO3, the Li source is Li2CO3, the Mn source is MnO2, the Bi source is Bi2O3, the Ta source is Ta2O5, and the Ce source is CeO2.

[0007] In step 1, the pre-sintering is performed in an air environment.

[0008] In step 1, 0.04≤x≤0.1, preferably 0.05<x≤0.1.

[0009] Step 2, mixing the pre-sintered materials uniformly, granulating, vacuum packaging, and warm isostatic pressing to obtain a green column; In step 2, the granulation uses a binder, and the ratio of the binder to the pre-sintered material is (2-5):1 by weight.

[0010] In the above technical solution, the adhesive is a polyvinyl alcohol (PVA) aqueous solution, and the polyvinyl alcohol (PVA) aqueous solution is a mixture of polyvinyl alcohol (PVA) and water. Calculated by mass, the ratio of water to polyvinyl alcohol in the polyvinyl alcohol (PVA) aqueous solution is (15~20):1.

[0011] In step 2, the vacuum packaging includes: column packaging at a pressure of 2-4 MPa.

[0012] In step 2, the pressure of the warm isostatic pressing is 30-50 MPa, the holding time of the warm isostatic pressing is 10-20 s, and the temperature of the warm isostatic pressing is 25-40°C.

[0013] In the above technical solution, the pressure increase rate of the warm isostatic pressing is 2~3MPa / s.

[0014] In step 1 and step 2, the mixing is performed uniformly by ball milling, the ball milling is wet milling, and the medium of wet milling is anhydrous ethanol.

[0015] In the above technical solution, the ball-to-material ratio of the ball mill is (3-5):1 by mass.

[0016] In the above technical solution, the wet grinding is followed by drying, the drying temperature is 70-80° C., and the drying time is 7-8 hours.

[0017] In the above technical solution, the rotation speed of the ball mill is 300-400 r / min, and the ball milling time is 8-12 h.

[0018] Step 3, debinding the green column, and performing a first sintering at 1000-1300° C. to obtain a ceramic material, wherein the first sintering time is 3-7 hours; In step 3, the temperature of the debinding treatment is 550-650° C., and the time of the debinding treatment is 0.5-2 h.

[0019] In step 3, the first sintering is performed in an air environment.

[0020] In the above technical solution, the heating rate to the temperature of 550-650°C is 3-5°C / min.

[0021] In step 3, the heating rate of heating to the temperature of 1000-1300° C. is 3-5° C. / min.

[0022] Step 4, coating the ceramic material with high-temperature silver paste (electrode), sintering for the second time (electrode sintering), and polarizing with high voltage in silicone oil in sequence to obtain a high-temperature piezoelectric ceramic material.

[0023] In step 4, the second sintering includes: keeping the temperature at 800-850° C. for 10-40 minutes in an air environment.

[0024] In step 4, the high voltage polarization in silicone oil includes: polarizing in silicone oil at 150-200° C. with a polarization field strength of 10-12 kV / mm for 30-40 minutes.

[0025] The high-temperature piezoelectric ceramic material obtained by the above preparation method.

[0026] Application of the above high temperature piezoelectric ceramic materials in acceleration sensors.

[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. The high temperature piezoelectric ceramic material of the present invention is prepared by composite ions (LiMn) 5+ Replace Ca element, Ce 4+ Replace Ta element and control Ce 4+ Compared with the calcium bismuth tantalate (CaBi2Ta2O9) based ceramic material, the present invention improves the piezoelectric constant, thermal stability and resistivity of the high-temperature piezoelectric ceramic material while ensuring that the Curie temperature does not drop, and reduces the dielectric loss. The Curie temperature of the high-temperature piezoelectric ceramic material of the present invention can reach up to 945°C, the piezoelectric constant at room temperature is as high as 15pC / N, the piezoelectric constant can still reach 13pC / N at 650°C, and the dielectric loss can be as low as 0.16%; 2. The temperature drift of the piezoelectric constant of the high-temperature piezoelectric ceramic material of the present invention is very small when it is at room temperature to 650°C, and the temperature drift of the piezoelectric constant is within 14%, that is, the high-temperature piezoelectric ceramic material of the present invention can operate stably for a long time at 650°C; the high-temperature piezoelectric ceramic material of the present invention has a small change in dielectric loss with temperature when it is at room temperature to 800°C; 3. The high temperature piezoelectric ceramic material of the present invention has a high resistivity of 10 at 650°C. 6 Ω●㎝, compared with calcium bismuth tantalate (CaBi2Ta2O9)-based ceramic materials, it has increased by two orders of magnitude at the same temperature, and has great application prospects in the field of high-temperature devices; 4. The preparation method of the present invention is simple, low-cost and suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The XRD diffraction patterns of the high-temperature piezoelectric ceramic materials prepared in Examples 1 to 6, wherein the inset is a partial enlarged view; Figure 2 The dielectric loss of the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 varies with temperature; Figure 3 This is a Curie temperature diagram of the high temperature piezoelectric ceramic material prepared in Example 4; Figure 4 This is a graph showing the variation of the piezoelectric constant of the high-temperature piezoelectric ceramic material prepared in Example 4 with temperature; Figure 5 The resistivity of the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 at 650°C. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0030] In the following examples and comparative examples, the Ca source is CaCO3, the Li source is Li2CO3, the Mn source is MnO2, the Bi source is Bi2O3, the Ta source is Ta2O5, the Ce source is CeO2, and the Na source is Na2CO3. CaCO3, Li2CO3, MnO2, Bi2O3, Ta2O5, CeO2, and Na2CO3 are all analytically pure.

[0031] High temperature silver paste: Xi'an Hongxingxing Electronic Paste Technology Co., Ltd., model C-1002.

[0032] The following piezoelectric constants, dielectric constants and dielectric losses are obtained at room temperature (20~25℃) unless otherwise specified.

[0033] The calculation method of the piezoelectric constant temperature drift is: ((piezoelectric constant at 650°C - piezoelectric constant at room temperature) / piezoelectric constant at room temperature) * 100%.

[0034] Embodiment 1~6

[0035] A method for preparing a high-temperature piezoelectric ceramic material comprises the following steps: Step 1, mixing Ca source, Li source, Mn source, Bi source, Ta source and Ce source to obtain a mixture, ball milling the mixture until it is uniformly mixed (ball milling adopts wet milling, the medium of wet milling is anhydrous ethanol, and the ratio of anhydrous ethanol to the mixture used in the ball milling in this step is 0.8:1, the speed of the ball milling is 300r / min, the ball milling time is 8h, and the ball-to-material ratio of the ball milling is 4:1 by mass), drying at 75°C for 8h, and pre-sintering at 850°C for 3h in an air environment to obtain a pre-sintered material, wherein, by mass, the ratio of Ca in the Ca source, Li in the Li source, Mn in the Mn source, Bi in the Bi source, Ta in the Ta source and Ce in the Ce source is A. The value of A is shown in Table 1; Table 1

[0036] Step 2, ball-mill the pre-sintered material until it is uniformly mixed (wet milling is adopted, and the medium of wet milling is anhydrous ethanol. In this step, the ratio of anhydrous ethanol to pre-sintered material is 0.8:1, the speed of ball milling is 300r / min, the time of ball milling is 8h, and the ball-to-material ratio of ball milling is 4:1), dry at 75°C for 8h, granulate, use dry pressing type tablet press to press column packaging (vacuum packaging) at 3MPa pressure, and warm isostatic press at 40MPa pressure for 10s ( The pressure increase rate of warm isostatic pressing is 3 MPa / s, and the temperature of warm isostatic pressing is 40°C), to obtain a green body column with a thickness of 13 mm and a diameter of 10 mm, wherein a binder is used for granulation, and the ratio of the binder to the pre-sintered material is 4:1 by weight, and the binder is a polyvinyl alcohol (PVA) aqueous solution, and the polyvinyl alcohol (PVA) aqueous solution is a mixture of polyvinyl alcohol (PVA) and water, and the ratio of water to polyvinyl alcohol (PVA) in the polyvinyl alcohol (PVA) aqueous solution is 18:1 by weight; Step 3, subjecting the green body column to a binder removal treatment at 650°C for 2h (heating rate to 650°C is 4°C / min) (to remove the binder and make the ceramic material have a certain hardness), and then sintering at 1180°C (first sintering) for 6h (heating rate to 1180°C is 4°C / min) in an air environment to obtain a ceramic material; Step 4, cut the ceramic material into ceramic sheets with a thickness of 0.6 mm, polish both sides of the ceramic sheets with 600 mesh sandpaper, and after polishing, coat the high-temperature silver paste on both sides of the ceramic sheets (electrode), and keep them at 850°C for 20 minutes in an air environment for a second sintering (electrode sintering). After the second sintering, polish and grind off the surface silver oxide on A4 paper to obtain a high-temperature piezoelectric ceramic material precursor, and polarize the high-temperature piezoelectric ceramic material precursor with high voltage in silicone oil to obtain a high-temperature piezoelectric ceramic material, wherein the high-voltage polarization in silicone oil includes: polarizing at a polarization field strength of 11 kV / mm for 40 minutes in silicone oil at 180°C (polarization field strength = polarization voltage (DC voltage) / thickness of the high-temperature piezoelectric ceramic material precursor).

[0037] Example 1 Piezoelectric constant of the high temperature piezoelectric ceramic material prepared d 33 =8pC / N, dielectric constant ε=68, dielectric loss tanδ=0.18%, resistivity ρ at 650℃=1.8×10 6 Ω●㎝.

[0038] Example 2 Piezoelectric constant of the high temperature piezoelectric ceramic material prepared d 33 =10pC / N, dielectric constant ε=69, dielectric loss tanδ=0.20%, resistivity ρ at 650℃=3.4×10 6 Ω●㎝.

[0039] Example 3 Piezoelectric constant of the high temperature piezoelectric ceramic material prepared d 33 =13pC / N, dielectric constant ε=71, dielectric loss tanδ=0.25%, resistivity ρ=5.6×10 at 650℃ 6 Ω●㎝.

[0040] Example 4 Piezoelectric constant of the high temperature piezoelectric ceramic material prepared d 33 =15pC / N, dielectric constant ε=69, dielectric loss tanδ=0.16%, resistivity ρ at 650℃=7.1×10 6 Ω●㎝.

[0041] Example 5 Piezoelectric constant of the high temperature piezoelectric ceramic material prepared d 33 =14pC / N, dielectric constant ε=70, dielectric loss tanδ=0.21%, resistivity ρ=5.8×10 at 650℃ 6 Ω●㎝.

[0042] Piezoelectric constant of the high temperature piezoelectric ceramic material prepared in Example 6 d33 =11pC / N, dielectric constant ε=68, dielectric loss tanδ=0.25%, resistivity ρ at 650℃=2.8×10 6 Ω●㎝.

[0043] The XRD diffraction patterns of the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 are as follows: Figure 1 As shown by Figure 1 It can be seen that the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 all have a typical Aurivillius phase structure, and all diffraction peaks can be indexed according to PDF card 72-2365. Figure 1 It can be seen that the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 do not have any second phase, indicating that Ce 4+ It has completely entered into CaBi2Ta2O9. The highest intensity diffraction peak corresponds to the (115) crystal plane, indicating that the high temperature piezoelectric ceramic material is a typical bismuth layered phase structure. Figure 1 As can be seen from the illustration, with the increase of Ce source dosage, the diffraction peak of (115) crystal plane first moves to the high 2 θ The angle direction is offset, and then to the lower 2 θ The angular direction is offset, indicating that different Ce source doping amounts will cause the lattice distortion of the high-temperature piezoelectric ceramic material.

[0044] The dielectric loss of the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 varies with temperature. Figure 2 As shown ( Figure 2 The vertical axis "loss" represents the dielectric loss, and the temperature range in the horizontal axis is from room temperature to 1000℃). Figure 2 It can be seen that within the temperature range of room temperature to 800° C., the dielectric loss of the high-temperature piezoelectric ceramic materials prepared in Examples 1 to 6 increases slowly with increasing temperature, which indicates that the high-temperature piezoelectric ceramic materials prepared in Examples 1 to 6 have excellent stability at high temperatures.

[0045] Example 4 The piezoelectric constant of the high temperature piezoelectric ceramic material prepared varies with temperature. Figure 4 As shown (temperature range: room temperature ~ 650 ° C, the high temperature piezoelectric ceramic material prepared in Example 4 is placed in a high temperature test furnace to test the change of piezoelectric constant with temperature), Figure 4 It can be seen that the piezoelectric constant of the high-temperature piezoelectric ceramic material prepared in Example 4 is 15 pC / N at room temperature, and the piezoelectric constant at 650° C. can still reach 13 pC / N, and the temperature drift of the piezoelectric constant is 13%.

[0046] The resistivity of the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 at 650°C is as follows: Figure 5 As shown by Figure 5It can be seen that the resistivity of the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 at 650°C is 10 6 Ω●㎝, and the resistivity ρ of the high temperature piezoelectric ceramic material prepared in Example 4 is as high as 7.1×10 6 Ω●㎝, the resistivity is the best.

[0047] Example 4 The Curie temperature of the high temperature piezoelectric ceramic material prepared is as follows Figure 3 As shown, the dielectric constant of the high-temperature piezoelectric ceramic material prepared in Example 4 gradually increases with the increase of temperature, reaches a peak value at 942°C, and then drops sharply, and its mutation temperature point is 942°C, which is the Curie temperature point of the high-temperature piezoelectric ceramic material prepared in Example 4.

[0048] The Curie temperature of the high temperature piezoelectric ceramic materials prepared in Examples 1 to 6 is T c ) as shown in Table 2.

[0049] Table 2

[0050] Comparative Examples 1 to 6

[0051] A method for preparing a piezoelectric ceramic material is basically the same as Example 1, except that: the mixed materials are different. The mixed materials of Comparative Examples 1 to 6 are all obtained by mixing a Ca source, a Li source, a Mn source, a Bi source and a Ta source. In terms of the amount of the substances, the ratio of Ca in the Ca source, Li in the Li source, Mn in the Mn source, Bi in the Bi source and Ta in the Ta source is B. The value of B is shown in Table 3.

[0052] Table 3

[0053] Piezoelectric constant of the piezoelectric ceramic material prepared in Comparative Example 1 d 33 =7.0pC / N, dielectric constant ε=68, dielectric loss tanδ=0.20%, Curie temperature T c =945℃, resistivity ρ at 650℃=7.2×10 5 Ω●㎝.

[0054] Piezoelectric constant of the piezoelectric ceramic material obtained in Comparative Example 2 d 33 =8.5pC / N, dielectric constant ε=69, dielectric loss tanδ=0.24%, Curie temperature T c =945℃, resistivity ρ at 650℃=8.9×10 5 Ω●㎝.

[0055] Piezoelectric constant of the piezoelectric ceramic material obtained in Comparative Example 3 d 33 =9.0C / N, dielectric constant ε=70, dielectric loss tanδ=0.27%, Curie temperature T c =945℃, resistivity ρ at 650℃=1.2×10 6 Ω●㎝.

[0056] Piezoelectric constant of the piezoelectric ceramic material obtained in Comparative Example 4 d 33 =12pC / N, dielectric constant ε=68, dielectric loss tanδ=0.21%, Curie temperature T c =940℃, resistivity ρ at 650℃=3.2×10 6 Ω●㎝.

[0057] Piezoelectric constant of the piezoelectric ceramic material obtained in Comparative Example 5 d 33 =11pC / N, dielectric constant ε=70, dielectric loss tanδ=0.27%, Curie temperature T c =940℃, resistivity ρ at 650℃=1.8×10 6 Ω●㎝.

[0058] Piezoelectric constant of the piezoelectric ceramic material obtained in Comparative Example 6 d 33 =10.5pC / N, dielectric constant ε=71, dielectric loss tanδ=0.22%, Curie temperature T c =940℃, resistivity ρ at 650℃=9.5×10 5 Ω●㎝.

[0059] Comparative Examples 7-12

[0060] A method for preparing a piezoelectric ceramic material is basically the same as that of Example 1, except that: the mixed materials are different. The mixed materials of Comparative Examples 7 to 12 are all obtained by mixing Ca source, Na source, Bi source, Li source, Ce source and Ta source to obtain a mixed material. In terms of the amount of the substances, the ratio of Ca in the Ca source, Na in the Na source, Bi in the Bi source, Li in the Li source, Ce in the Ce source and Ta in the Ta source is C. The value of C is shown in Table 4.

[0061] Table 4

[0062] The stoichiometric formula of the piezoelectric ceramic material in Comparative Examples 7 to 12 is Ca 0.5 (Na0.5 Bi 0.5 ) 0.5-y (Li 0.5 Ce 0.5 ) y Bi2Ta2O9, in Comparative Examples 7 to 12, y The values ​​are 0.01, 0.03, 0.05, 0.07, 0.09 and 0.11 respectively. The piezoelectric ceramic materials prepared in Comparative Examples 7 to 12 are (Li 0.5 Ce 0.5 ) 2.5+ Replacement (Na 0.5 Bi 0.5 ) 2+ , and the composite ion (LiMn) of the embodiment of the present invention 5+ Replace Ca and Ce 4+ The elements replacing Ta are different.

[0063] Piezoelectric constant of the piezoelectric ceramic material prepared in Comparative Example 7 d 33 =8.2pC / N, dielectric constant ε=70, dielectric loss tanδ=0.22%, Curie temperature T c =945℃, resistivity ρ at 650℃=8.8×10 5 Ω●㎝.

[0064] Piezoelectric constant of the piezoelectric ceramic material prepared in Comparative Example 8 d 33 =9.0pC / N, dielectric constant ε=70, dielectric loss tanδ=0.22%, Curie temperature T c =945℃, resistivity ρ at 650℃=1.3×10 6 Ω●㎝.

[0065] Piezoelectric constant of the piezoelectric ceramic material prepared in Comparative Example 9 d 33 =11.5pC / N, dielectric constant ε=71, dielectric loss tanδ=0.27%, Curie temperature T c =945℃, resistivity ρ at 650℃=2.8×10 6 Ω●㎝.

[0066] Piezoelectric constant of the piezoelectric ceramic material prepared in Comparative Example 10 d 33 =12.5pC / N, dielectric constant ε=72, dielectric loss tanδ=0.19%, Curie temperature T c=940℃, resistivity ρ at 650℃=4.2×10 6 Ω●㎝.

[0067] Piezoelectric constant of the piezoelectric ceramic material prepared in Comparative Example 11 d 33 =12pC / N, dielectric constant ε=72, dielectric loss tanδ=0.21%, Curie temperature T c =940℃, resistivity ρ at 650℃=3.0×10 6 Ω●㎝.

[0068] Piezoelectric constant of the piezoelectric ceramic material prepared in Comparative Example 12 d 33 =11pC / N, dielectric constant ε=73, dielectric loss tanδ=0.24%, Curie temperature T c =940℃, resistivity ρ at 650℃=1.1×10 6 Ω●㎝.

[0069] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a high-temperature piezoelectric ceramic material, characterized in that: The following steps are involved: Step 1, mixing a Ca source, a Li source, a Mn source, a Bi source, a Ta source and a Ce source to obtain a mixture, mixing the mixture evenly, and pre-sintering at 850-950° C. for 2-4 hours to obtain a pre-sintered material, wherein, in terms of the amount of substance, the ratio of Ca in the Ca source, Li in the Li source, Mn in the Mn source, Bi in the Bi source, Ta in the Ta source and Ce in the Ce source is 0.5:0.5:0.5:2:(2-0.4x):x, wherein 0.03<x<0.11; Step 2, mixing the pre-sintered materials uniformly, granulating, vacuum packaging, and warm isostatic pressing to obtain a green column; Step 3, debinding the green column, and performing a first sintering at 1000-1300° C. to obtain a ceramic material, wherein the first sintering time is 3-7 hours; Step 4: coating the ceramic material with high-temperature silver paste, sintering for a second time, and polarizing with high voltage in silicone oil in sequence to obtain a high-temperature piezoelectric ceramic material.

2. The preparation method according to claim 1, characterized in that: In step 2, the granulation uses a binder, and the ratio of the binder to the pre-sintered material is (2-5):1 by weight.

3. The preparation method according to claim 2, characterized in that: The adhesive is a polyvinyl alcohol aqueous solution, which is a mixture of polyvinyl alcohol and water. In terms of mass fractions, the ratio of water to polyvinyl alcohol in the polyvinyl alcohol aqueous solution is (15-20):

1.

4. The preparation method according to claim 1, characterized in that: In step 2, the vacuum packaging includes: column packaging at a pressure of 2-4 MPa.

5. The preparation method according to claim 1, characterized in that: In step 2, the pressure of the warm isostatic pressing is 30-50 MPa, the holding time of the warm isostatic pressing is 10-20 s, and the temperature of the warm isostatic pressing is 25-40°C.

6. The preparation method according to claim 1, characterized in that: In step 3, the temperature of the debinding treatment is 550-650° C., and the time of the debinding treatment is 0.5-2 h.

7. The preparation method according to claim 1, characterized in that: In step 4, the second sintering includes: keeping the temperature at 800-850° C. for 10-40 minutes in an air environment.

8. The preparation method according to claim 1, characterized in that: In step 4, the high voltage polarization in silicone oil includes: polarizing in silicone oil at 150-200° C. with a polarization field strength of 10-12 kV / mm for 30-40 minutes.

9. A high temperature piezoelectric ceramic material obtained by the preparation method according to any one of claims 1 to 8.

10. Application of the high temperature piezoelectric ceramic material as claimed in claim 9 in an acceleration sensor.

Citation Information

Patent Citations

  • Lithium-cerium-tantalum codoping niobic acid-bismuth-calcium based piezoceramic material and preparation method thereof

    CN103922722A

  • Lithium, cerium, tungsten (Li, Ce, W) co-doped bismuth calcium niobate (CBN)-based piezoelectric ceramic material and preparation method thereof

    CN103936418A

  • Bismuth layer-structured piezoelectric ceramic material and preparation method thereof

    CN104529435A

  • Doped and modified bismuth calcium niobate-based ceramic material and preparation method thereof

    CN114507070A

  • Production of piezoelectric ceramics

    JP2001048647A